INTEGRASI KURIKULUM MERDEKA BELAJAR DENGAN KURIKULUM PESANTREN PADA MATA PELAJARAN AKIDAH AKHLAQ DI MA ALAWIYAH - Maulidiyah, Nurlaila; Muhammad, Devy Habibi (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
Education is a process of forming human personality, both through religious and general processes. According to Law no. 20 of 2003 education is an effort and is planned to create an atmosphere of an active learning process and increase its potential. The Merdeka Curriculum is a learning design that provides students with the opportunity to feel safe, relaxed, have fun, learn without pressure, and develop their talents in the process. Islamic boarding schools are a type of Islamic religious educational institution in Indonesia which has an educational system that is different from other religious educational institutions, such as madrasas. The leadership of the Alawiyah Islamic Boarding School has an important role in carrying out curriculum management. The curriculum base used at MA.Alawiyah refers to the curriculum organized by the government (independence curriculum) and the Islamic boarding school curriculum. Researchers used research with a qualitative phenomenological approach to describe the meaning of the integration of the independent and Islamic boarding school curriculum in learning moral beliefs.